Mineral content of coffee of different altitudes from the State of Guerrero, México - Antúnez Ocampo, Oscar Martín; Puente-Valenzuela, Cristo Omar; Espinosa-Rodríguez, Mariana; Sabino-López, Juan Elías; Flores-Hernández, Luis Antonio (Ecosistemas y Recursos Agropecuarios, 2025)
In Montaña, Costa Grande and Chica regions of Guerrero State, Mexico; The coffee (Coffea arabica L.) cultivation is an important strategic activity for indigenous and farmers population. Altitude is a factor one that influences in the biochemical composition, physical and organoleptic quality of the cup coffee. The objective was to evaluate the macro and micronutrients content in ground roasted coffee from different altitudes of Guerrero State. The treatments were six coffees collected at different altitudes in Guerrero. The experimental design was completely randomized, with four repetitions. The coffees were collected in the towns and municipalities of: i) San Miguel el Progreso and Paraje Montero, Malinaltepec; ii) Páscala del Oro, San Luis Acatlán; iii) El Carrizal, Tlacoapa and iv) Barranca Pobre, Acatepec. K, Ca, Fe and Cu were analyzed by direct aspiration in air-acetylene flame, in an Analyst700 PerkinElmer® atomic absorption spectrometer; N and P were quantified with a Jenway® 73 UV/VIS spectrophotometer, values were expressed in in percentage (%) and mg kg-1. The highest content of N and Cu was recorded in coffee of 2041 m; however, in coffees at lower altitudes (1 060 and 1 089 m) there were higher P, K and Fe levels. The 1 986 m coffee stood out in Ca (0.17%). Altitude was a factor that differentiated the mineral content of ground roasted coffee, where the abundance order were K, N, P, Ca, Fe and Cu.
Keywords: Altitude; quality; Coffe arabica; Guerrero; toasted; minerals